The Influence of Organizational Culture and Work Competence on the Performance of Baznas Employees of Riau Islands Province with Job Satisfaction as a Mediating Variable - Nurhayati; Cecep Yoto Haryoto (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to test and analyze the Influence of Organizational Culture and Work Competence on Employee Performance at Baznas Riau Islands Province with Job Satisfaction as a mediating variable. The independent variables used are Organizational Culture and Work Competence, while the dependent variable is Employee Performance. Job Satisfaction is used as a mediating variable.The data collection method in this study was carried out by distributing questionnaires to 150 respondents who were employees of Baznas Riau Islands Province. This study uses a quantitative approach with an associative research type. The data obtained were processed using the Structural Equation Modeling (SEM) analysis model based on Partial Least Square (SmartPLS).The results of the study indicate that Organizational Culture has a positive and significant effect on Job Satisfaction with a coefficient value of 0.498, and Job Competence has a positive and significant effect on Job Satisfaction with a coefficient value of 0.343. Organizational Culture has a positive and significant effect on Employee Performance with a coefficient value of 0.155, and Job Competence has a positive and significant effect on Employee Performance with a coefficient value of 0.107. Job Satisfaction has a positive and significant effect on Employee Performance with a coefficient value of 0.311. In addition, Organizational Culture has a positive and significant effect on Employee Performance through Job Satisfaction with a coefficient value of 0.444, and Job Competence has a positive and significant effect on Employee Performance through Job Satisfaction with a coefficient value of 0.180.